Assessing cytokine status of patients with chronic endometritis combined with endometrial hyperplastic processes in reproductive period - L. V. Tkachenko (Sankt-Peterburg : NIIÈM imeni Pastera, 2020)
The goal of our study was to examine local and serum cytokine level involved in regulating inflammation in patients with chronic endometritis combined with endometrial hyperplastic processes. On admission, all patients underwent hysteroscopy with separate diagnostic curettage followed by histological examination of samples isolated from the uterine and cervical canal mucosa. Such manipulations were indicated due to abnormal uterine bleeding as well as suspected endometrial pathology based on ultrasound examination. According to the histological examination data of the endometrial samples, all patients were divided into two groups: group I contained 45 women with CE combined with PEG without atypia; group II — 38 patients with morphologically verified CEE combined with AEG without atypia. Level of IL-1P, IL-2, IL-6, IFNy, TNFa in biological fluids (aspirate from the uterus; serum) was measured by using enzyme-linked immunosorbent assay. We found that in both groups (91.1% and 89.6%, respectively) the vast majority of patients was hospitalized due to abnormal uterine bleeding. Oligomenorrhea alternated with intermenstrual bleeding (66.7% and 71.2%, respectively) and dominated in pattern of menstrual cycle disorders in the examined patients, whereas 11 (24.4%) and 7 (18.4%) patients from group I and II, respectively, were noted to suffer from severe menstrual bleeding. Overall, analyzing the data on cytokine level both in the uterine aspirate and serum evidences about ongoing inflammatory process found at examination time point. Upon that, such process was not only local, but also exhibited signs of a systemic inflammatory response. The data on cytokine level in the uterine aspirate from patients with CE coupled to PGE or CGE without atypia point at local inflammatory process characterized by significantly increased concentration of IL-ф, IL-2, IL-6, TNFa and IFNy. At the same time, higher level of IL-ф and IFNy in patients from group II might indicates that degree of morphological changes in the endometrium could affect the level of local cytokine production. Thus, the data obtained evidence that immune changes in chronic endometritis combined with non-atypical endometrial hyperplastic processes mostly occur locally. In this regard, measuring cytokine concentration in the uterine aspirate is a diagnostic predictor and serves as a sign for monitoring therapeutic effectiveness of therapy in this cohort of patients.